Development of BIM-Framework for evaluating the Energy-Saving Design Criteria in South Korea - Choi, Chang-Ho; Hong, Soung-Wook; Kim, Chang-Min; Jang, Hyang-In (International Journal of Engineering and Technology, 2019)
Although South Korea introduced ‘Energy-saving design criteria’ for efficient building energy management, floor plan processing is required because a detailed item evaluation is performed based on 2D floor plans, which leads to a decrease in work productivity. Therefore, the purpose of this study is to develop an evaluation framework based on the BIM model to save time and increase efficiency in order to prepare energy saving plans in South Korea, and verify its effectiveness through a comparative analysis with conventional evaluation methods. The results are as follows. 1) The process and input/output information was derived by classifying the evaluation items according to BIM data requirement information, and the BIM evaluation framework was developed based on Architecture Revit 2015. 2) For each item, error rates occurred for the calculated value of the BIM-based evaluation framework compared to conventional evaluation methods. 3) The score for each item of the BIM-based energy saving design criteria evaluation framework was the same as the conventional evaluation method. Therefore, the BIM-based evaluation framework developed in this study was considered to be a method to evaluate the energy saving design criteria.